2011
DOI: 10.1136/hrt.2010.219345
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection against ischaemia induced by dobutamine stress using glucagon-like peptide-1 in patients with coronary artery disease

Abstract: ISRCTN 69686930.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 34 publications
5
65
0
8
Order By: Relevance
“…Sokos et al (34) reported that a long-term infusion of GLP-1 improves both LV ejection fraction and functional capacity in human patients with advanced heart failure (34). This is in agreement with another pilot study showing that treatment with GLP-1 improved LV function in patients with coronary artery disease (28).…”
Section: Discussionsupporting
confidence: 78%
“…Sokos et al (34) reported that a long-term infusion of GLP-1 improves both LV ejection fraction and functional capacity in human patients with advanced heart failure (34). This is in agreement with another pilot study showing that treatment with GLP-1 improved LV function in patients with coronary artery disease (28).…”
Section: Discussionsupporting
confidence: 78%
“…33 In coronary artery disease patients with good LV function, a continuous infusion of rGLP-1 for 30 minutes before dobutamine stress echocardiography demonstrated an improved ejection fraction and LV regional wall function as well as mitigated post-ischaemic stunning, predominantly in the ischaemic wall segment. 42 The beneficial effect of a 72-hour GLP-1 infusion on the postinfarction recovery, including an increased ejection fraction and improvement of both global and regional wall motion was also observed in acute myocardial infarction patients with LV ejection fraction of less than 40% after successful primary percutaneous coronary intervention. 43 Long-term GLP-1 infusion also improved myocardial stunning, which was characterised by enhanced LV wall motion and relaxation in I/R dogs.…”
Section: Effects Of Glp-1 On Left Ventricular Functionmentioning
confidence: 99%
“…73 Acute infusion of GLP-1 (1.2 pmol/kg per minute) 30 minutes before dobutamine stress echocardiography and continuing for 30 minutes into recovery in 14 patients with stable coronary artery disease and normal resting LV function prevented the development of postischemic myocardial dysfunction. 74 Moreover, the infusion of GLP-1 (1.2 pmol/ kg per minute) after completion of the first balloon occlusion reduced LV dysfunction during dual-inflation balloon angioplasty in 20 nondiabetic patients with single-vessel coronary artery disease. 75 Lønborg et al 76 investigated the effects of a 6-hour exenatide or placebo infusion (mean plasma concentration of exenatide was 0.177±0.069 nmol/L) initiated 15 minutes before reperfusion onset in 172 patients undergoing percutaneous coronary intervention to treat ST-segment elevation MI.…”
Section: Clinical Studiesmentioning
confidence: 99%